High serum levels of IL-2R, IL-6, and TNF-α are associated with higher tumor burden and poorer outcome of follicular lymphoma patients in the rituximab era. (July 2020) - Mozas, Pablo; Rivas-Delgado, Alfredo; Rivero, Andrea; Dlouhy, Iván; Nadeu, Ferran; Balagué, Olga; González-Farré, Blanca; Baumann, Tycho; Giné, Eva; Delgado, Julio; Villamor, Neus; Campo, Elías; et al.
Highlights: Elevated cytokine levels correlated with tumor burden and high-risk disease. High cytokine levels impacted on a shorter PFS and OS. High TNF-α levels were an independent predictor of a shorter PFS. The determination of cytokine levels in FL patients is feasible in clinical practice. Abstract: The clinical behavior of FL patients is heterogeneous. The levels of sIL-2R have been correlated with tumor burden and outcome in FL. However, the impact of IL-6 and TNF-α in this disease is unclear. We studied 253 patients diagnosed with grade 1-3a FL between 2002 and 2018, with available information on serum levels of sIL-2R, IL-6, and TNF-α at diagnosis. Patients with cytokine levels above the cutoff had features of a higher tumor burden and higher-risk disease. Levels of any of the studied cytokines above the cutoff and a higher number of cytokines above the cutoff impacted on a shorter PFS and OS. TNF-α levels were an independent predictor of a poorer PFS. No differences were observed in the risk of histological transformation or second malignancies. The determination of cytokine levels in FL patients is feasible in clinical practice, and elevated levels are associated with a higher tumor burden and poorer survival.